3050 Engagement in Out-Patient Services among Pregnant and Postpartum Women with Opioid Addiction: A Qualitative Study. (27th March 2019) - Peacock-Chambers, Elizabeth; Paterno, Mary T.; Kiely, Daniel; Fioroni, Tinamarie; Friedmann, Peter D.
Abstract : OBJECTIVES/SPECIFIC AIMS: This study aims to understand the factors influencing engagement with out-patient services from pregnancy to 1 year postpartum among women in recovery from opioid use disorders (OUD). METHODS/STUDY POPULATION: We conducted semi-structured qualitative interviews and a brief survey with 20 mothers in OUD recovery recruited from health care and community organizations in Western MA. Transcripts were coded by two independent coders and analyzed using a qualitative descriptive approach. RESULTS/ANTICIPATED RESULTS: The average duration of any addiction treatment among the 20 participants was 5.6 years with 80% receiving medication-assisted treatment during a pregnancy. Approximately two-thirds experienced relapse during pregnancy or the first year postpartum. We identified 3 themes elucidating women's experiences around service engagement: "How I see myself" (personal development), "How services see me" (service delivery quality), and "Are you with me?" Personal development included response to past trauma, coping strategies and self-advocacy, and adjusting to parenthood. Service delivery quality was influenced by service design, efficacy of individual providers, and cultural norms (organizational and societal). In the final theme, intersection of individual and service-level factors influenced the degree and quality of the women's experience engaging with services. DISCUSSION/SIGNIFICANCE OF IMPACT: Women describe successful engagement when they experience service providers as being emotionally supportive, delivering relevant services, and advocating on their behalf. To best support and engage families affected by OUD, relevant and timely services should be linked with compassionate delivery.